Holocene palynological correlation between Baby Tuktu Lake, southern Hall Peninsula, Baffin Island, N.W.T., Canada and Brevoort Basin, Davis Strait - Escamilla, Marci A. (Northern Illinois University, 1994)
Includes bibliographical references (pages [80]-85) A marine core from Brevoort Basin in Davis Strait, and a Baby Tuktu Lake core from southern Hall Peninsula on Baffin Island were analyzed for pollen content. Correlation between the two cores was accomplished by using the palynostratigraphy of each core. Subsequently, limiting radiometric dates determined by linear interpolation between radiocarbon dated levels were applied to each core. The marine core comprises six pollen-assemblage zones. The lower three zones pre-date the lowest zone in Baby Tuktu Lake core one. Zone BVT-6 consists of a low Arctic shrub-birch tundra, indicative of ice-free conditions and influx of palynomorphs from the deglaciated Labrador- Ungava coast. The assemblage of zone BVT-5 indicates an herbaceous tundra, and probably reflects the Cockburn substage glacial advance. Zone BVT-4 is a sedge-dominated pollen assemblage in which pre-Quaternary spores decline to modern levels, indicative of decreased input of older sediment eroded from the continental shelf. Correlation between the two cores first occurs between zone BVT-3 of the marine core and zone BTL-3 of the lacustrine core. The pollen assemblage is of a low Arctic birch-shrub tundra which suggests an amelioration of climate, and is believed to represent the local Hypsithermal. The decline in birch during correlative zones BVT-2 and BTL-2 indicates deterioration of climate after the Holocene climatic optimum. Zone BVT-1 is correlative with zone BTL-1 and reflects the modern mid- Arctic shrub assemblage on southern Baffin Island. Because the core sites are only sixty km apart, the zone boundaries should be synchronous. After correlating the two cores using only the pollen assemblage zones, correlation of the Baby Tuktu Lake core with the Brevoort Basin core was done using limiting radiometric dates. Correlation using the adjusted absolute chronology produces a closer match between the two cores in the upper zones, but produces further division at lower levels. Dates on both cores are questionable due to geologically old carbon introduced into the basins through various mechanisms and rapidly changing conditions produced by the disintegration of the Laurentide Ice Sheet. Hence, for these reasons absolute chronologies on marine and lacustrine cores are problematic. M.S. (Master of Science)